The Application of The Susan Loucks-Horsley Learning Model with a Contextual Approach to Static Fluid Material to Improve Concept Understanding Class XI High School Students - Ramadhani, Ramadhani; Rahmad, M.; Ernidawati, Ernidawati (Journal of Educational Sciences, 2024)
The problem found from interviews with physics teachers at SMAN 1 Gaung who said that students' understanding of physics material was still low. This is due to the use of learning models that have not been varied so that students' understanding of physics concepts is still low. Efforts to improve students' concept understanding can be applied through learning using the Susan Loucks-Horsley model with a contextual approach. This study aims to improve students' concept understanding. The type of research used is quasi-experimental design with non-equivalent control group design. The population in this study were students of class XI MIPA SMAN 1 Gaung. The samples used were XI MIPA 1 class as the experimental class and XI MIPA 2 class as the control class taken by random sampling which had gone through normality and homogeneity tests. Data were determined through tests that were prepared based on seven indicators of concept understanding. Data were analyzed descriptively and inferentially to determine the category of explanation of students' concept understanding. The research results obtained from the N-gain test score in the experimental class amounted to 0.7 and the control class amounted to 0.3. The score results show that the understanding of the concept of experimental class students is higher than the control class. This research can be concluded that the Susan Loucks-Horsley model with a contextual approach can improve the understanding of the concept of students of class XI MIPA SMAN 1 Gaung.